A high-integration patterned printing method and application
Through the elastomeric substrate-assisted stencil printing method, combined with the stress tensile and resilience of the first substrate, the problem of limited integration of patterned arrays in the prior art is solved, and high-precision, high-integration, micro-nano structure manufacturing with submicron-level line width and line spacing is realized, which is suitable for the manufacturing of flexible electronic devices.
Patent Information
- Application Number
- CN202111387165.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-22
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-11-22
AI Technical Summary
It is difficult for existing stencil printing technology to achieve the construction of high-integration patterns. The line spacing is limited by the template accuracy and the airflow during the assembly process, making it difficult to achieve high-precision, high-integration, micro-nano structure manufacturing at submicron level.
Using a high-integration stencil printing method assisted by elastomeric substrate, a micro-nano structure is directly constructed on the first substrate with adjustable thickness, and a high-precision patterned array preparation is achieved by applying stress to the first substrate.
It realizes a nanoparticle array with a maximum line spacing of submicrons and a high-resolution organic functional material array, breaking through the limitations of lithography accuracy in conventional printing technology. It has high precision, high integration and flexibility characteristics, and is suitable for the manufacturing of flexible electronic devices.
Smart Images

Figure CN114751365B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of printing of functional materials, in particular, to a high-integration patterned printing method and application, and specifically to a high-integration template printing method assisted by an elastomer substrate and the application of a patterned array. Background Art
[0002] Advanced patterned micro-nanofabrication technology is essential to promote the miniaturization and integrated preparation of functional devices, such as field effect transistors, sensors and display devices. As a typical micro-nanofabrication manufacturing technology, photolithography is widely used to prepare electronic devices with high-resolution circuits. However, photolithography has the disadvantages of cumbersome processing steps, high energy consumption, high cost and limited material applicability. In the past few decades, some alternative micro-nanofabrication manufacturing processes, such as nanoimprinting, nanotransfer, template printing and dip-pen nanolithography, have been effectively developed. In particular, the "bottom-up" template printing technology has attracted widespread attention. Template printing technology can achieve the preparation of nanometer-level precision patterns using micron-level templates, and the general line precision can reach submicron, hundreds of nanometers or even tens of nanometers. In addition to being able to prepare high-resolution patterns independent of templates, template printing also has the advantages of simple operation, low energy consumption, low cost, and wide applicability of materials / substrates, especially providing a method for high-precision patterning that can be processed in solution. This technology is expected to have a revolutionary impact on high-precision manufacturing and device integration. However, the pattern spacing is still limited by the accuracy of the photolithography template preparation process and the impact of the airflow on the liquid bridge shrinkage during the assembly process, which is basically 5 to 10 microns. The manufacture of micro-nano structures with both submicron-level high precision and high integration is very challenging. Therefore, it is urgent to develop high-precision, high-integration, multi-dimensional patterned solution processing technology, which will be of great significance to the basic research and practical application in the process of promoting device miniaturization and integration.
[0003] CN103253629B discloses a method for orderly assembly of template-printed nanoparticles; the method uses optical etching to obtain a hard template with a microarray structure; ink containing functional materials is dropped on a flat substrate, and the hard template containing the microarray is covered; the template, ink and substrate form a "sandwich" structure, and the functional material is induced by the template, and the solution slides along the solid-liquid-gas three-phase line to form a liquid bridge between the microcolumns. As the solvent evaporates, the liquid bridge drives the functional material to shrink and finally gather into a patterned array. This method can prepare the functional material into a regular one-dimensional array structure. However, the line spacing is limited by the template, and it is difficult to achieve the construction of a high-integration pattern. Summary of the invention
[0004] The purpose of the present invention is to overcome the common problem of limited integration of patterned arrays in printing technology. On the one hand, it provides the patterned construction of different functional materials (metal functional materials, inorganic non-metal functional materials, organic functional materials, composite functional materials) on the surface of the first substrate; on the other hand, with the assistance of the elastomeric substrate (i.e., the first substrate) and combined with the resilience of the substrate, a nanoparticle array with a spreading morphology with a line spacing of up to submicron and a one-dimensional array of organic functional materials (such as PEDOT:PSS) and composite functional materials (such as sodium alginate SA / Ga) with a dewetting morphology with significantly improved spacing resolution are successfully constructed. The line spacing in conventional plate printing technology is limited by the accuracy of photolithography technology, and a high-precision and high-integration micro-nano structure patterned array that can simultaneously achieve submicron line width and line spacing is prepared. In addition, since the micro-nano structure is directly constructed on the first substrate with adjustable thickness, it is conducive to realizing the non-planar structure, symmetrical or asymmetrical stretching characteristics of the micro-nano structure, which can meet the requirements for flexible electronic devices; at the same time, it has the advantages of being green and environmentally friendly, simple to prepare, and low cost. This method will provide strong technical support for the high-precision patterned assembly of solution-processable functional materials, the high-density integrated preparation of functional devices, and the research on their performance and applications.
[0005] In order to achieve the above object, the present invention provides a method for preparing a patterned array, the method comprising the following steps:
[0006] 1) preparing a second substrate containing a microstructure array and subjecting the substrate to high-energy radiation treatment;
[0007] 2) dissolving the first substrate raw material in an organic solvent to prepare a first substrate having a hydrophilic group on the surface;
[0008] 3) applying stress to the first substrate in step 2) to keep the first substrate in a stretched state;
[0009] 4) adding a solution containing a functional material to the surface of the first substrate maintained in a stretched state in step 3);
[0010] 5) superimposing the second substrate after the radiation treatment in step 1) on the first substrate in step 4), so that the second substrate, the solution containing the functional material and the first substrate form a "sandwich" structure;
[0011] 6) After the solvent in the "sandwich" structure evaporates, the first substrate and the second substrate are separated to release the first substrate, thereby preparing a patterned array.
[0012] The present invention also provides another method for preparing a patterned array, the method comprising:
[0013] (S1) dissolving a first substrate raw material in an organic solvent to prepare a first substrate having a hydrophilic group on its surface;
[0014] (S2) applying stress to the first substrate in step (S1) so that the first substrate remains in a stretched state;
[0015] (S3) Printing the solution containing the functional material directly on the surface of the first substrate maintained in the stretched state in step (S2), releasing the first substrate, and preparing a patterned array.
[0016] In step 6) of the present invention, the second substrate is removed to release the first substrate, thereby obtaining a high-precision and high-integration patterned array.
[0017] According to the present invention, step 1) and steps 2)-4) can be performed simultaneously or sequentially, or step 2)-4) can be performed first and then step 1), which will not affect the implementation of the present invention. It is only necessary to complete step 1) or steps 2)-4) before step 5).
[0018] According to the present invention, in step (5), the second substrate treated with radiation may be placed on the first substrate, or the first substrate may be placed on the second substrate treated with radiation.
[0019] According to the present invention, in step 1), the second substrate is a hard substrate or a soft substrate. Preferably, the hard substrate is selected from one of silicon wafer, aluminum sheet, copper sheet, glass sheet, quartz sheet, polyethylene terephthalate (PET), polymethyl methacrylate (PMMA), polyimide (PI), and the hard substrate can be prepared into a regular microstructure array by photolithography technology; preferably, the soft substrate is selected from one of hydrogel, polydimethylsiloxane (PDMS), ECOFLEX; the soft substrate can be prepared into a regular microstructure array by soft etching technology.
[0020] According to the present invention, in step 1), on the second substrate, there is no limitation on the shape of the microstructure array unit and the composition of each unit, and it can be designed according to requirements, and the microstructure array unit is selected from one of a linear microwall structure, a nonlinear microwall structure, a microcylindrical structure and an arbitrary polygonal microcylindrical structure. Exemplarily, the width W of each array unit in the linear microstructure array can range from 1 to 10 μm, and the spacing D is 1 to 20 μm; preferably, the width W is 1 to 4 μm, and the spacing D is 2 to 15 μm. Exemplarily, the width W is 2 μm, and the spacing D is 3 μm or 10 μm.
[0021] According to the present invention, in step 2) or step (S1), the first substrate is a flexible substrate having certain tensile strength, elongation at break, toughness and surface hardness, and can be a thermoplastic elastomer, a thermosetting elastomer and a hydrogel. Exemplarily, at least one selected from styrene-butadiene-styrene block copolymer (SBS), styrene-ethylene-butadiene-styrene block copolymer (SEBS), styrene-isopropylene-styrene block copolymer (SIS), polyurethane (PU) (including thermoplastic polyurethane (TPU)), ethylene-octene copolymer (POE), thermoplastic polyester elastomer (TPEE), polyimide (PI), polydimethylsiloxane (PDMS), silicone rubber (ECOFLEX), natural rubber (NR), styrene-butadiene rubber, nitrile rubber, PDMS / ECOFLEX composite material, PDMS / TPU composite material, ECOFLEX / TPU composite material, polyethylene glycol hydrogel, polyvinyl alcohol hydrogel, polyacrylic acid and its derivatives hydrogel, polyoxyethylene hydrogel, polyacrylamide hydrogel, polyhydroxyethyl methacrylate hydrogel, polyacrylic acid hydrogel, polymethacrylic acid hydrogel, and polyphosphazene hydrogel.
[0022] According to the present invention, in step 2) or step (S1), the contact angle of the first substrate is 20° to 70°.
[0023] According to the present invention, in step 2) or step (S1), the hydrophilic group is, for example, at least one of a carboxylic acid group, a sulfonic acid group, a sulfate group, a phosphoric acid group, an amino group, a quaternary ammonium group, an ether group, a hydroxyl group, a carboxylate group, and the like.
[0024] According to the present invention, in step 2) or step (S1), the mass concentration of the first substrate raw material is 5-50%, preferably 10-40%, and more preferably 20-30%.
[0025] According to the present invention, in step 2) or step (S1), the first substrate raw material refers to solid particles or liquid compounds containing the first substrate. Exemplarily, when the first substrate is a polyurethane film, the raw material of the first substrate is a polyurethane masterbatch.
[0026] According to the present invention, in step 2) or step (S1), the first substrate having a surface containing hydrophilic groups can be prepared by one or more of a surfactant blending method and a high-energy radiation treatment method.
[0027] Illustratively, the steps of the surfactant blending method for hydrophilization treatment are: mixing the first substrate raw material with the surfactant and the organic solvent, and preparing a film, namely the first substrate.
[0028] According to the present invention, when the surfactant blending method is used for hydrophilization treatment, the mass concentration of the surfactant is 0.5% to 10%, preferably 2.0% to 4.5%. The surfactant is a polysoap surfactant and a water-soluble polymer surfactant. Exemplarily, anionic surfactants selected from carboxylic acid type, sulfate type, and sulfonic acid type; cationic surfactants of amine salts, polyamines and quaternary ammonium salts; zwitterionic surfactants of acrylic acid vinyl pyridine copolymers, acrylic acid and amphoteric polyacrylamide; amphoteric surfactants of polyvinyl alcohol and its modified polyacrylamide, maleic anhydride copolymer, polyacrylate, polyether, water-soluble phenolic resin, amino resin; non-ionic surfactants such as fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, fatty amine polyoxyethylene ether, alkyl alcohol amide polyoxyethylene ether, block polyoxyethylene-polyoxypropylene ether, alkyl alcohol amide, alkylphenol polychlorinated ether. Further preferred is one of sodium dodecyl sulfate, alkylphenol polyoxyethylene ether (exemplary may be nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether), cetyltrimethylammonium bromide, nonylphenol polychlorinated ether, polyvinyl alcohol, polyethylene glycol octyl ether, octadecyl alcohol, and polyisobutylene-maleic anhydride copolymer.
[0029] According to the present invention, in step 1) and step 2), in the high-energy radiation treatment, the high-energy radiation high energy source used is selected from one of plasma, α-rays, γ-rays, and ultraviolet rays. Preferably, the high-energy radiation high energy source used is selected from plasma, and the conditions for plasma treatment include: time of 5 to 300 s, power of 5 to 200 W, and further preferably, time of 20 to 80 s, power of 10 to 80 W. Exemplarily, the power is 5 W, 10 W, 15 W, 20 W, 30 W, 50 W, 70 W, 80 W, 100 W, 120 W, 150 W, 170 W, 180 W or 200 W.
[0030] According to the present invention, in step 2) or step (S1), the organic solvent is one or more of N,N-dimethylformamide, acetamide, butanone, cyclohexanone, acetone, ethyl acetate, toluene and xylene.
[0031] According to the present invention, in step 3) or step (S2), when the first substrate is in a stretched state, its pre-strain can be set according to the mechanical properties of different substrates, such as tensile strength, tear strength, surface hardness, elongation at break, rebound rate and other properties. Exemplarily, it is 1% to 500%, preferably 30% to 400%, and more preferably 50-300%.
[0032] As shown in the embodiments and comparative examples of the present invention, the present invention achieves changes in line width and line spacing by applying pre-strain to the first substrate, and can realize the preparation of high-precision and high-integration patterned arrays.
[0033] According to the present invention, in step 4) or step (S3), the solution containing the functional material includes 0.1wt%-0.3wt% of a surfactant, preferably 0.1wt%-0.2wt%, 0.5wt%-18wt% of a functional material, preferably 0.5wt%-15wt%, and the rest is a solvent; illustratively, the content of the functional material is 0.5wt%, 1wt%, 2wt%, 4wt%, 5wt%, 7wt%, 8wt%, 10wt%, 14wt%, 15wt% or 18wt%.
[0034] In the present invention, there is no particular limitation on the type of the functional material, which can be appropriately selected as needed. Preferably, the functional material is selected from one or more of metal functional materials, inorganic non-metal functional materials, organic functional materials, and composite functional materials.
[0035] Preferably, the metal functional material may be a pure metal, an alloy, an intermetallic compound, or a special metal material, and the morphology of the metal is not limited, and may be nanoparticles, nanowires, or nanosheets, for example, one or more selected from the group consisting of gold, silver, platinum, copper, germanium, nickel, titanium, aluminum, selenium, molybdenum, arsenic, tellurium, cadmium, antimony, indium, tin, gallium-indium alloy, and gallium-indium-tin alloy.
[0036] Preferably, the inorganic non-metallic functional material is selected from one or more of zinc oxide, quantum dots, silicon nanoparticles, titanium dioxide particles, silicon dioxide particles, aluminum oxide, iron oxide, Janus particles, polystyrene microspheres, graphene, graphyne, carbon nanotubes, Mxene, molybdenum selenide, gallium arsenide, gallium nitride, cadmium telluride, and barium titanate.
[0037] Preferably, the organic functional material may be an organic conjugated / non-conjugated small molecule, an organic conjugated / non-conjugated polymer, or an organic functional high molecular material. One or more selected from tetraphenylethylene (TPE) and its derivatives, organic semiconductor material N2200, perylene imide and its derivatives, porphyrin and its derivatives, carbazole and its derivatives, naphthylimide and its derivatives, poly(3,4-ethylenedioxythiophene): poly(styrene sulfonate) (PEDOT:PSS), polyacetylene, polyaniline and its derivatives, polypyridine and its derivatives, polythiophene and its derivatives, poly(9,9-di-n-octylfluorenyl-2,7-diyl), poly(3-hexylthiophene), sodium poly(p-styrene sulfonate) (PSSNa), lithium bis(trifluoromethanesulfonyl)imide, 4-(3-butyl-1-imidazole)-1-butanesulfonic acid trifluoromethanesulfonate, poly(p-styrene), polyphenylene vinyl, polystyrene (PS), polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), PMMA, polycaprolactone (PCL), and polylactic acid (PLA).
[0038] Preferably, the composite functional material is selected from one or more of PEDOT:PSS / PSSNa, sodium alginate / gallium, PSSNa / silver nanoparticles, lithium bis(trifluoromethanesulfonyl imide) / silver nanoparticles, silicone oil / gallium-indium alloy, silicone oil / gallium-indium-tin alloy, ECOFLEX / gallium-indium alloy, ECOFLEX / gallium-indium-tin alloy, PDMS / gallium-indium alloy, and PDMS / gallium-indium-tin alloy.
[0039] According to the present invention, when the solution containing the functional material is a nanoparticle solution having a spreading morphology, exemplarily a silver nanoparticle solution, the applied pre-strain is 1% to 500%, preferably 30% to 400%, and more preferably 50-300%;
[0040] When the solution containing the functional material is a polymer solution with a dewetting morphology, exemplarily a solution containing PEDOT:PSS or a solution containing liquid metal gallium coated with sodium alginate, the applied pre-strain is 1% to 140%, preferably 30% to 100%.
[0041] According to the present invention, the solvent in the solution containing the functional material is an organic solvent, water or an organic solvent diluted with water. Preferably, the organic solvent is one or more of acetone, benzene, toluene, xylene, chlorobenzene, dichlorobenzene, dichloromethane, ethylene glycol monomethyl ether, ethylene glycol, ethanol, methanol and isopropanol.
[0042] According to the present invention, in step 4) or step (S3), the solution containing the functional material can be added to the surface of the first substrate in a dropwise manner.
[0043] According to the present invention, in step 5), on the same horizontal plane, the second substrate is placed in a direction in which the microstructure array is oriented perpendicular to the tensile stress.
[0044] According to the present invention, in step 6), the "sandwich" structure is subjected to a temperature of 20 to 60° C. to remove the solvent from the solution containing the functional material. The time for removing the solvent is not limited, as long as the solvent can be completely removed. Exemplarily, it is 1 to 10 hours.
[0045] According to the method of the present invention, the dimension of the patterned array can be prepared according to the template of the corresponding microstructure, and the dimension is not limited. It can be a zero-dimensional patterned array, a one-dimensional patterned array, a two-dimensional patterned array or a three-dimensional patterned array. That is, the patterned arrays of different dimensions can be prepared by the above method.
[0046] In the present invention, the integration density of the template-printed patterned array and the precision of the microstructure can be improved by the flexible stretchability and resilience of the first substrate. The present invention is not limited to template printing, and can be appropriately selected according to needs, preferably, one or more of inkjet printing, screen printing, 3D printing, direct writing technology, transfer printing, gravure printing, electrospray printing, electroplating, nanoimprinting, and etching technology.
[0047] The present invention also provides a highly integrated patterned array prepared by the above method.
[0048] The present invention also provides an application of the above-mentioned patterned array, characterized in that it is applied to optoelectronic devices, smart sensors, electronic skin, photonic skin, smart skin, conformal antennas, flexible wearable devices, supercapacitors, energy collection devices, self-powered friction nanogenerators, high-sensitivity sensors, photoelectric detection devices, gratings, organic light-emitting diodes, solar cells, waveguides, field effect transistors, flexible thin film electrodes or biochips.
[0049] Beneficial Effects
[0050] The present invention is a method based on template printing, and a microarray containing functional materials is prepared on a first substrate. By hydrophilizing the first substrate, metal functional materials, inorganic non-metallic functional materials, organic functional materials or composite functional materials can be assembled, and the resilience of the flexible first substrate can be used to further improve the integration density of template printing and the resolution of the microstructure. The preparation method of the present invention is simple, green and environmentally friendly, low in cost, and has the advantages of high pattern refinement and integration. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 is a partially enlarged scanning electron microscope image of the array in Example 1 of the present invention;
[0052] Figure 2 is a partially enlarged scanning electron microscope image of the array in Example 2 of the present invention;
[0053] Figure 3 is a partially enlarged scanning electron microscope image of the array in Example 3 of the present invention;
[0054] Figure 4 is a partially enlarged scanning electron microscope image of the array in Example 4 of the present invention;
[0055] Figure 5 is a partially enlarged scanning electron microscope image of the array in Comparative Example 1 of the present invention;
[0056] Figure 6 is a partially enlarged scanning electron microscope image of the array in Comparative Example 2 of the present invention;
[0057] Figure 7is a partially enlarged scanning electron microscope picture of the array in Comparative Example 3 of the present invention;
[0058] Figure 8 is a partially enlarged scanning electron microscope image of the array in Comparative Example 4 of the present invention;
[0059] Fig. 9 is a partially enlarged optical microscope picture of the array in Example 5 of the present invention;
[0060] Fig.10 It is a partially enlarged optical microscope picture of the array in Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0061] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0062] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0063] Example 1
[0064] (1) Preparation of the flexible first substrate
[0065] Weigh an appropriate amount of polyurethane masterbatch (TPU) and dissolve it in N, N-dimethylformamide (DMF) solvent to prepare a solution with a mass concentration of 25%, add octylphenol polyoxyethylene ether with a mass concentration of 2.0%, and prepare a polyurethane film by blade coating so that the contact angle value is in the range of 35°-50°;
[0066] (2) Preparation of solutions containing functional materials
[0067] Using silver nanoparticles with a particle size of about 30-50 nm, sodium dodecyl sulfate (SDS) and deionized water to prepare a solution containing silver nanoparticles, wherein the mass concentration of the silver nanoparticles is 3%, and the mass concentration of SDS is 0.2%;
[0068] (3) Preparation of high-precision and high-integration patterned arrays
[0069] The TPU film was cut into strips of 8 cm in length and 3 cm in width. A stretching device was used to apply stress to the strips, stretching them to a strain of 300% and keeping them fixed. The second substrate silicon wafer template was treated with plasma at a power of 15 W for 30S-50S, wherein the microstructure array on the second substrate silicon wafer template was a linear microwall structure, each array unit was 2 microns wide and 3 microns apart. A microsyringe was used to draw 1-5 μL of a solution containing silver nanoparticles and dripped it onto the polyurethane film. On the same horizontal plane, the second substrate silicon wafer template treated with plasma was placed in a direction perpendicular to the tensile stress in which its microstructure orientation was perpendicular to the tensile stress. The first substrate, the solution containing silver nanoparticles and the second substrate formed a "sandwich" structure. Then the template was transferred to a constant temperature environment of 50°C and kept for about 3 hours. Finally, the second substrate was removed, the TPU substrate was released, and a one-dimensional silver nanoparticle line array assembled with high precision was obtained, realizing the preparation of a line array with submicron precision using a micron-level template, with the line width reduced from 2 microns to about 0.8 microns and the spacing reduced from 3 microns to about 0.9 microns. Within a limited area, the integration density is greatly increased.
[0070] Example 2
[0071] (1) Preparation of the flexible first substrate
[0072] Weigh an appropriate amount of TPU masterbatch and dissolve it in DMF solvent to prepare a solution with a mass concentration of 25%, add octylphenol polyoxyethylene ether with a mass concentration of 2.0%, and prepare a polyurethane film by blade coating to make the contact angle value within the range of 35°-50°;
[0073] (2) Preparation of solutions containing functional materials
[0074] Prepare an aqueous solution of conductive polymer PEDOT:PSS, wherein the mass concentration of PEDOT:PSS is 1.0% and the mass concentration of SDS is 0.2%;
[0075] (3) Preparation of high-precision and high-integration patterned arrays
[0076] The TPU film was cut into strips of 8 cm in length and 2 cm in width, and the strips were stressed and stretched to 100% and fixed. The second substrate silicon wafer template was plasma treated with a power of 60 W for 50S-70S, wherein the microstructure array on the second substrate silicon template was a linear microwall structure, each array unit was 2 microns wide and 10 microns apart. 1-5 μL of the solution containing PEDOT:PSS was drawn with a microsyringe and dripped onto the polyurethane film. On the same horizontal plane, the plasma-treated silicon template was placed in a direction perpendicular to the microstructure orientation and tensile stress, and the second substrate, the solution containing PEDOT:PSS functional materials and the flexible first substrate formed a "sandwich" structure. Then it was transferred to a constant temperature environment of 50°C and kept for about 3 hours. Finally, the second substrate was removed and the TPU substrate was released to obtain a high-precision assembled PEDOT:PSS linear array, with the spacing reduced from 10 microns to about 6.5 microns.
[0077] Example 3
[0078] (1) Preparation of the flexible first substrate
[0079] Weigh an appropriate amount of TPU masterbatch and dissolve it in DMF solvent to prepare a solution with a mass concentration of 25%, add octylphenol polyoxyethylene ether with a mass concentration of 2.0%, and prepare a polyurethane film by blade coating to make the contact angle value within the range of 35°-50°;
[0080] (2) Preparation of solutions containing functional materials
[0081] A solution of liquid metal gallium coated with sodium alginate is prepared, wherein the mass concentration of gallium is 5% and the mass concentration of SDS is 0.2%;
[0082] (3) Preparation of high-precision and high-integration patterned arrays
[0083] The TPU film was cut into strips of 8 cm in length and 2 cm in width, and the strips were stressed and stretched to 100% and fixed. The second substrate silicon wafer template was plasma treated with a power of 60 W for 50S-70S, wherein the microstructure array on the second substrate silicon wafer template was a linear microwall structure, each array unit was 2 microns wide and 10 microns apart. 1-5 μL of a solution containing functional materials was drawn using a microsyringe and dripped onto the polyurethane film. On the same horizontal plane, the plasma-treated silicon template was placed in a direction perpendicular to the microstructure orientation and tensile stress, and the second substrate, the solution containing functional materials and the flexible first substrate formed a "sandwich" structure. Then it was transferred to a constant temperature environment of 50°C and kept for about 3 hours. Finally, the second substrate was removed, the TPU substrate was released, and a high-precision assembled linear array of liquid metal gallium was obtained, with the spacing reduced from 10 microns to about 6.4 microns.
[0084] Example 4
[0085] The difference between Example 4 and Example 1 is that in step (3), the pre-strain applied to the TPU film substrate is 200%. After the substrate is released, the line spacing of the silver nanoparticle linear array is reduced from 3 microns to about 1.3 microns, and the line width is reduced from 2 microns to about 0.8 microns.
[0086] Example 5
[0087] (1) Preparation of the flexible first substrate
[0088] Weigh an appropriate amount of polyurethane masterbatch (TPU) and dissolve it in N, N-dimethylformamide (DMF) solvent to prepare a solution with a mass concentration of 25%, add octylphenol polyoxyethylene ether with a mass concentration of 2.0%, and prepare a polyurethane film by blade coating so that the contact angle value is in the range of 35°-50°;
[0089] (2) Preparation of solutions containing functional materials
[0090] Prepare a chlorobenzene solution of N2200, wherein the mass concentration of N2200 is 0.5% and the mass concentration of SDS is 0.2%;
[0091] (3) High-precision direct writing printing
[0092] The TPU spline (same size as in Example 1 above) was stretched to 100% strain and kept fixed. The N2200 solution was printed directly on the stretched TPU spline using a direct write printer. The print needle diameter was 50 microns, and the print spacing was set to 400 microns. After printing, the TPU substrate was released to obtain a one-dimensional N2200 line array with significantly improved accuracy. The line width was reduced from 194 microns to about 126 microns, and the spacing was reduced from 200 microns to about 129 microns. Within the same area, the number of line arrays increased significantly.
[0093] Comparative Example 1
[0094] The difference between Comparative Example 1 and Example 1 is that in step (3), no stress is applied to the TPU film substrate, so that the strain is always maintained at 0%, and a silver nanoparticle linear array is obtained, and the array width and spacing are limited by the size of the template microstructure.
[0095] Comparative Example 2
[0096] The difference between Comparative Example 2 and Example 2 is that in step (3), no stress is applied to the TPU film substrate, so that the strain is always maintained at 0%, and a linear array of PEDOT:PSS is obtained, and the array spacing is limited by the size of the template microstructure.
[0097] Comparative Example 3
[0098] The difference between Comparative Example 3 and Example 3 is that in step (3), no stress is applied to the TPU substrate, so that the strain is always maintained at 0%, and a linear array of liquid metal gallium is obtained, and the array width and spacing are limited by the size of the template microstructure.
[0099] Comparative Example 4
[0100] The difference between Comparative Example 4 and Example 3 is that in step (3), the pre-strain applied to the TPU film substrate is 150%, and the assembly line breaks after the substrate is released. It is difficult for the array with dewetting morphology to withstand a large pre-strain.
[0101] Comparative Example 5
[0102] The difference between Comparative Example 5 and Example 5 is that in step (2), no stress is applied to the TPU substrate so that the strain is always maintained at 0%, and the line array of N2200 is printed. Due to the extrusion swelling effect of the solution, the line width and spacing are 194 and 200 microns respectively.
[0103] The resolution tests of the functional material line arrays prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were compared. The resolution test included the width of a single assembly line in each array unit (line width) and the spacing between line arrays (line spacing). The test results are shown in Table 1.
[0104] Table 1 Line width and line spacing of the line arrays prepared in Examples 1 to 4 and Comparative Examples 1 to 3
[0105]
[0106]
[0107] It can be seen from the above embodiments and comparative examples that the line width and spacing of the patterned array of 1D silver nanoparticles with a spreading morphology prepared by the present invention will be reduced at the same time after the substrate is released, and will break through the submicron (see Example 1 and Comparative Example 1, Example 4); the line width of the patterned array of 1D polymers and composite functional materials with a de-wetting morphology (for example, a solution containing PEDOT:PSS or a solution containing liquid metal gallium coated with sodium alginate) does not change much, but the spacing is significantly reduced (see Examples 2 and 3 and Comparative Examples 2 and 3). In addition, the array with a de-wetting morphology is easily damaged and broken after the substrate is released under a large pre-strain (see Comparative Example 4). It can be seen from these embodiments that whether the line width is reduced is related to the morphology of the line. The spreading morphology or the de-wetting morphology is different, and the line width changes are also different under the same prestress conditions. Moreover, the spreading morphology can withstand a larger pre-strain than the de-wetting morphology. In addition, the method and flexible substrate of the present invention are also suitable for improving the accuracy and integration of direct writing printing technology.
[0108] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a patterned array, characterized in that: The method comprises the following steps: 1) preparing a second substrate containing a microstructure array and subjecting it to high-energy radiation treatment; in the high-energy radiation treatment, the radiation source is plasma; 2) dissolving the first substrate raw material in an organic solvent to prepare a first substrate having a hydrophilic group on the surface; 3) applying stress to the first substrate in step 2) to keep the first substrate in a stretched state; 4) adding a solution containing a functional material to the surface of the first substrate maintained in a stretched state in step 3); 5) superimposing the second substrate after the radiation treatment in step 1) on the first substrate in step 4), so that the second substrate, the solution containing the functional material and the first substrate form a "sandwich" structure; 6) After the solvent in the "sandwich" structure evaporates, the first substrate and the second substrate are separated to release the first substrate, thereby preparing a patterned array; In step 3), when the first substrate is in a stretched state, the pre-strain is 200% to 400%; In step 4), the solution containing the functional material is a 1D silver nanoparticle solution having a spreading morphology; The width W of each array unit in the patterned array is 1~4μm, and the spacing D is 2~15μm; The patterned array is a one-dimensional patterned array.
2. A method for preparing a patterned array, characterized in that: The method comprises the following steps: (S1) dissolving a first substrate raw material in an organic solvent to prepare a first substrate having a hydrophilic group on its surface; (S2) applying stress to the first substrate in step (S1) so that the first substrate remains in a stretched state; (S3) directly printing a solution containing a functional material onto the surface of the first substrate maintained in a stretched state in step (S2), releasing the first substrate, and preparing a patterned array; In step (S2), when the first substrate is in a stretched state, the pre-strain is 200% to 400%; In step (S3), the solution containing the functional material is a 1D silver nanoparticle solution having a spreading morphology; The width W of each array unit in the patterned array is 1~4μm, and the spacing D is 2~15μm; The patterned array is a one-dimensional patterned array.
3. The method according to claim 1, characterized in that In step 1), the second substrate is a hard substrate or a soft substrate, the hard substrate is selected from one of silicon wafer, aluminum sheet, copper sheet, glass sheet, quartz sheet, polyethylene terephthalate, polymethyl methacrylate, and polyimide; the soft substrate is selected from one of hydrogel, polydimethylsiloxane, and ECOFLEX; The array unit is selected from one of a linear micro-wall structure, a nonlinear micro-wall structure, a micro-cylindrical structure and an arbitrary polygonal micro-cylindrical structure; The plasma treatment time is 5 to 300 seconds, and the power is 5 to 200W.
4. The method according to claim 1 or 2, characterized in that: In step 2) or step (S1), the first substrate is a flexible substrate selected from at least one of styrene-butadiene-styrene block copolymer, styrene-ethylene-butadiene-styrene block copolymer, styrene-isopropylene-styrene block copolymer, polyurethane, ethylene-octene copolymer, thermoplastic polyester elastomer, polyimide, polydimethylsiloxane, silicone rubber, natural rubber, styrene-butadiene rubber, nitrile rubber, PDMS / ECOFLEX composite material, PDMS / TPU composite material, ECOFLEX / TPU composite material, polyethylene glycol hydrogel, polyvinyl alcohol hydrogel, polyacrylic acid and its derivatives hydrogel, polyoxyethylene hydrogel, polyacrylamide hydrogel, polyhydroxyethyl methacrylate hydrogel, polyacrylic acid hydrogel, polymethacrylic acid hydrogel, and polyphosphazene hydrogel.
5. The method according to claim 1 or 2, characterized in that: In step 2) or step (S1), the contact angle of the first substrate is 20° to 70°; in step 2) or step (S1), the organic solvent is at least one of acetamide, N,N-dimethylformamide, butanone, cyclohexanone, acetone, ethyl acetate, toluene, and xylene; In step 2) or step (S1), the hydrophilic group is at least one of a carboxylic acid group, a sulfonic acid group, a sulfate group, a phosphoric acid group, an amino group, a quaternary ammonium group, an ether group, a hydroxyl group, and a carboxylate group; In step 2) or step (S1), the mass concentration of the first substrate raw material is 5-50%; In step 2) or step (S1), the first substrate raw material refers to solid particles or liquid compounds containing the first substrate; in step 2) or step (S1), the first substrate containing hydrophilic groups on the surface is prepared by one or more of a surfactant blending method and a high-energy radiation treatment method.
6. The method according to claim 1 or 2, characterized in that: In step 4) or step (S3), the solution containing the functional material includes 0.1wt%-0.3wt% of a surfactant, 0.5wt%-18wt% of the functional material, and the rest is a solvent.
7. The method according to claim 6, characterized in that The solvent in the solution containing the functional material is one or more of water, acetone, benzene, toluene, xylene, chlorobenzene, dichlorobenzene, dichloromethane, ethylene glycol monomethyl ether, ethylene glycol, ethanol, methanol, and isopropanol.
8. The method according to claim 1 or 2, characterized in that: In step 4) or step (S3), the solution containing the functional material is added to the surface of the first substrate in a dropwise manner.
9. The method according to claim 1, characterized in that: In step 5), on the same horizontal plane, the second substrate is placed in a direction perpendicular to the tensile stress in which the microstructure array is oriented; In step 6), the "sandwich" structure is heated at 20-60° C. to remove the solvent from the solution containing the functional material.
10. The method according to claim 1, characterized in that The method is suitable for template printing.
11. The method according to claim 1, characterized in that: The method is also applicable to one or more of inkjet printing, screen printing, 3D printing, direct writing printing, transfer printing, gravure printing, electrospray printing, electroplating, nanoimprinting, and etching technologies.
12. The patterned array prepared by the method of claim 1 or 2.
13. Application of the patterned array according to claim 12 in optoelectronic devices, smart sensors, electronic skin, photonic skin, smart skin, conformal antennas, flexible wearable devices, supercapacitors, energy harvesting devices, self-powered friction nanogenerators, high-sensitivity sensors, photodetection devices, gratings, organic light-emitting diodes, solar cells, waveguides, field effect transistors, flexible thin film electrodes or biochips.
Citation Information
Patent Citations
Nano particle precise ordered assembling method
CN103253629B
Nano particle precise order assembling method
CN103253629A
Method for preparing micro-nano structure on elastic substrate
CN109437091A
Method of one-dimensional co-assembly by micron and / or nanoparticles with different particle sizes, substrate and application
CN109553063A
Micro-nano material self-assembly method, substrate and application
CN110065925A